Spiritualitas Persaudaraan Imam Diosesan sebagai Dasar Identitas dan Kesetiaan Pelayanan Imamat - Lenjau, Dominikus (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2025)
This study aims to understand the spirituality of diocesan priestly fraternity as the foundation of priestly identity and ministry within the context of a diverse and geographically vast local Church. Using a descriptive qualitative approach, it explores the lived experiences of priests in a diocese in Kalimantan in embodying fraternity values, confronting pastoral challenges, and discerning the theological meaning of communal life. Data were collected through literature review, documentation, and semi-structured interviews with 17 diocesan priests and analyzed thematically and reflectively. The findings reveal that priestly fraternity is manifested in three main dimensions: presbyteral communion as the basis of priestly identity, daily fraternal practices that nurture solidarity, and ongoing formation mechanisms that sustain vocational fidelity. Challenges such as geographical isolation, generational differences, and individualistic tendencies serve as opportunities for spiritual growth and renewal in relationships. The study highlights the distinct contribution of this research by clarifying the conceptual linkage between the three dimensions as an integrated model of diocesan priestly fraternity. The study concludes that the spirituality of fraternity is not merely a moral requirement but a theological foundation that animates the identity and pastoral mission of diocesan priests in the life of the Church.